ОРГАНІЗАЦІЙНО-ЕКОНОМІЧНИЙ МЕХАНІЗМ УПРАВЛІННЯ ПРОЦЕСАМИ ЕНЕРГОЗАБЕЗПЕЧЕННЯ ДІЯЛЬНОСТІ ПІДПРИЄМСТВ З ВИКОРИСТАННЯМ НЕТРАДИЦІЙНИХ І ВІДНОВЛЮВАНИХ ДЖЕРЕЛ ЕНЕРГІЇ - Ільницький, Д. Є.; Палійчук, У. Ю.; Псюк, Р. М.; Мельницький, М. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
In the article on the basis of comparative analysis of conceptual and theoretical principles of structuring of, formation and improvement of organizationally-economic mechanisms of management of enterprises as a whole as well as enterprises by separate functionally necessary subdivisions the possibilities were explored and recommendations were formulated on the creation of a subsystem of energy supply of the enterprise of a specialized unit for implementation of non-traditional and renewable energy sources focused on environmental and economic improvement indicators of its activities.